Associations between dietary, lifestyle behavioural practices and quality of life among malay survivors of breast cancer in Kelantan - Ping, Rebecca Wong Leh (Universiti Sains Malaysia, 2015)
Understanding the dietary and lifestyle practices among survivors of breast cancer are important in order to improve the general health and wellbeing, and quality of life. However, little is known about the effects of diet and lifestyle practices after diagnosis on breast cancer survival. Therefore, the main aim of the present study was to determine the dietary and lifestyle practices and its impact on the quality of life among 92 Malay survivors of breast cancer living in Kelantan. Pre-piloted questionnaire was used to assess the socio-economic status, dietary and lifestyle-related behavioural practices, whereas quality of life (QoL) of the participants were assessed using validated Malay-version of the the EORTC QLQ-C30 and its breast cancer module BR23. Nutrient intake of the participants was assessed using semi-quantitative food frequency questionnaire (FFQ) of 15 food groups commonly consumed foods in Kelantan. The mean age of the participants were 49.8 ±8.1, with the mean body mass index (BMI) of 26.2 ± 4.9. More than half of them (53.2%) were classified as overweight and obese. Dietary practices after diagnosis of cancer showed that majority of the participants (65.2%) were generally consumed snacks at least once in a day and majority were preferred to consume food prepared in frying method (62.0%). The use of nutrition food label among these participants was low, whereby majority of the participants were never or rarely read the nutrition label contained in foods packaging. The median duration of time spent on vigorous activity by the participants was only 0.3 hours/day [95 % Cis: 0.3-0.6], where 0.5 hours/day [95 % Cis: 0.4-0.7] was spent on light activity. Analysis of habitual physical activity (PA) and sedentarybased activity practices showed that almost two-thirds of the participants (69.6%) were engaged in moderate PA levels with only 28.3% of them were physically active. Pearson correlation analysis showed there was significant difference between BMI with QOL subscales of physical functioning (r=-0.336; p<0.01) and lower body image (r=-0.237; p<0.05). Further analysis was conducted to examine the differences between nutrients profile and survival status among these participants, it showed that there was a significant difference in essential nutrients intake between breast cancer survival years, in which participants with higher survival status of > 5 had significantly higher intake of dietary protein (p<0.005), carbohydrate (p<0.05), calories (p<0.05), total fiber (p<0.05), essential omega-6 fatty acids (p<0.05), calcium (p<0.005), iron (p<0.05) and vitamin C (p<0.05) compared with those with shorter survival years of less than 5 y. In conclusion, majority of these participants were still practicing unhealthy dietary and lifestyle practices, despite being diagnosed with breast cancer. Majority of them were preferred to consume foods high in fat, and nutrition concern such as the use of nutrition label of packaged food consumed among them was also low. Continuous efforts and strategies of healthy eating and active lifestyle practices should be promoted among survivor of cancers in order to maintain optimal health and general well-being of these populations.